A Quantified Methodology for Evaluating Engineering Sustainability: Ecological Footprint Measurement Modeling - Jinli Jiang; Xiaojuan Li; Liyan Yu; Jianqiang Jin; Xian Liang (Buildings)
With the gradual increase in public awareness of ecological environmental protection, how to manage the increasingly tight supply of natural ecological energy and resources and the more evident greenhouse effect, how to properly treat and deal with the relationship between people, engineering and the ecological environment during the construction phase of engineering projects as well as how to evaluate the degree of environmental friendliness and sustainable development ability of engineering projects will become an urgent issue. Stakeholders in engineering projects must seriously consider these vital issues. Existing studies on the evaluation of engineering–ecology sustainable development capacity mainly focus on the regional and industry levels, with less research focusing on the sustainability of individual engineering projects; furthermore, they are primarily concentrated on the qualitative evaluation perspective. In order to refine these shortcomings, based on the viewpoint of the ecosystem of construction projects, this paper integrates the concept of whole life cycle with the ecological footprint measurement model and defines the notion of the ecological footprint of the whole life cycle of construction projects. Subsequently taking the above concept as the foundation and making the ecological footprint of various activities throughout the life cycle of a construction project a specific study object, the research establishes the ecological footprint measurement model of the whole life cycle of the project, and comprehensively evaluates the impacts on the surrounding environment, which include the consumption of energy resources, CO2 and the absorption of solid wastes across the whole life cycle of the project. We then measure the sustainable development ability of engineering projects by comparing the ecological footprint with the ecological carrying capacity of a certain surrounding region. Finally, the practicability and reliability of the model is verified through the example’s application. Thus, the results of the study have significant theoretical and practical implications: (1) the introduction of the ecological footprint addresses the gap about the quantitative evaluation of the sustainability of individual engineering projects from a micro perspective; (2) it compensates for the shortcomings of other evaluation methods that only evaluate a single element, such as only CO2, resources, energy or solid waste and so on; and (3) stakeholders can use the measured model to quantitatively assess the sustainability of new projects or urban renewal projects, providing strong support for project feasibility studies and project-establishment.